Maestro Lucio Diestro San Pedro the creative nationalist - Hila, Antonio C.; Orellana, Ricky; De la Cruz, Libertine Santos (Kuwadro., 2002)
Features the compositions, arrangements, performances, and the civic activities of Lucio D. San Pedro. A wide-ranging body of his works includes band music, concertos for violin and orchestra, choral works, cantatas, chamber music, for violin and piano, and songs for solo voice. His works are refined in the crucible of Filipino sensibility and Western classical technique. Sa Ugoy ng Duyan, a lullaby, and Sa Mahal Kong Bayan, a song, are conceded by many to be exquisite distillations of the Filipino soul.